Preparing for inclusive teaching : meeting the challenges of teacher education reform - Bondy, Elizabeth; Ross, Dorene Doerre (Albany, NY : State University of New York Press, 2005)
"Grounded in the reform effort of a large state university with a history of excellence in teacher education, this book provides teacher educators and institutions with a valuable resource for navigating the choppy waters of reform. Contributors, all involved in the reform process, tell the story of the University of Florida's efforts in the mid-1990s to unify general and special education in its teacher education program. The book examines various aspects of the reform process, explains challenges faced by teacher educators within today's context and particularly within the context of large research institutions, presents strategies leaders use to keep reform on track in spite of challenges, and includes detailed descriptions of the nature and structure of the reformed program. Also included are valuable insights of teacher education experts from other institutions to contextualize the particulars of this reform within the national education and teacher education scenes."--Jacket
Foreword / Catherine Emihovich -- Introduction / Elizabeth Bondy [and others] -- PART 1: AN INTRODUCTION TO REFORM IN TEACHER EDUCATION -- Mapping the reform agenda in teacher education: the challenges for teacher educators / Peter L. Rennert-Ariev [and others] -- Barriers to teacher education reform: lessons from the literature and from experience / Rodman B. Webb -- PART 2: REFORM AT THE UNIVERSITY OF FLORIDA -- Description of the unified elementary special education proteach program / Dorene D. Ross [and others] -- Designing the program: an overview of the process / Vivian I. Correa [and others] -- The field experiences: teaching in partnership with schools and community / Cynthia C. Griffin [and others] -- Cross-departmental teaching teams / Rodman B. Webb [and others] -- The unified elementary program: discussion and critique / Marleen C. Pugach -- PART 3: PARTICIPANT PERSPECTIVES -- Communication and conflict on three teaching teams / Mary T. Brownell [and others] -- Learning in partnerships: the experience of students, teachers, and college faculty / Elizabeth Bondy [and others] -- Joining the conversation about families and teaching: counselor educators' perspectives on teacher preparation / Ellen S. Amatea, Joanna Jennie -- Learning from students' perspectives on courses and field experiences / Elizabeth Bondy [and others] -- Views from the inside: an ousider's perspective / Renee Tipton Clift -- PART 4: STUDENT AND PROGRAM EVALUATION -- Performance assessment: overview of challenges and directions / Catheryn Weitman -- Performance assessment / Sharen Halsall, Theresa B. Vernetson -- The electronic portfolio project / Gail Ring [and others] -- PART 5: THE REFORM IN CONTEXT -- A special educator's reflections on teacher education reform / Linda Blanton -- A general teacher educator's reflections / Alan R. Tom -- The unified elementary program: response from a school-based perspective / Diane W. Kyle, Gayle H. Moore.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: University of Florida. -- College of Education -- Case studies; University of Florida. -- College of Education; Teachers -- Training of -- Florida -- Gainesville -- Case studies; Inclusive education -- United States; Interdisciplinary approach in education -- Florida -- Gainesville -- Case studies; Intégration scolaire -- États-Unis.; Interdisciplinarité en éducation -- Floride -- Gainesville -- Études de cas; Enseignants -- Formation -- Floride -- Gainesville -- Études de cas; EDUCATION -- Research; Inclusive education; Interdisciplinary approach in education; Teachers -- Training of; Florida -- Gainesville; United States; Case studies